2021
DOI: 10.1021/acs.jctc.1c00135
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Molecular Emitters in Organic Light-Emitting Diodes with the Quantum Mechanical Bespoke Force Field

Abstract: Combined molecular dynamics (MD) and quantum mechanics (QM) simulation procedures have gained popularity in modeling the spectral properties of functional organic molecules. However, the potential energy surfaces used to propagate long-time scale dynamics in these simulations are typically described using general, transferable force fields designed for organic molecules in their electronic ground states. These force fields do not typically include spectroscopic data in their training, and importantly, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Consequently, the apparent larger MAE of the hh‐TDA approach for singlet excitation energy compared to TD‐DFT is not inherent to the method itself. Indeed, while the correspondence between the hh‐TDA/B3LYP MAE value of 0.66 eV for the D‐A compounds in Scheme 2 and the Stokes shift of ≈0.6 eV of PTZ‐DBTO2 [ 61,64 ] is simply fortuitous, this comparison gives a feeling of the error order being induced into the MAE values by considering the absorption onset energies of the DA compounds instead of their emission energies, error which has nothing to do with the performances of the hh‐TDA method. Nevertheless, the hh‐TDA/B3LYP approach exhibits the highest correlation of 0.84 for D‐A TADF.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Consequently, the apparent larger MAE of the hh‐TDA approach for singlet excitation energy compared to TD‐DFT is not inherent to the method itself. Indeed, while the correspondence between the hh‐TDA/B3LYP MAE value of 0.66 eV for the D‐A compounds in Scheme 2 and the Stokes shift of ≈0.6 eV of PTZ‐DBTO2 [ 61,64 ] is simply fortuitous, this comparison gives a feeling of the error order being induced into the MAE values by considering the absorption onset energies of the DA compounds instead of their emission energies, error which has nothing to do with the performances of the hh‐TDA method. Nevertheless, the hh‐TDA/B3LYP approach exhibits the highest correlation of 0.84 for D‐A TADF.…”
Section: Resultsmentioning
confidence: 98%
“…These effects also manifest in the Stokes shift stemming from structural changes in the emitter, which, in the case of PTZ‐DBTO2 molecule, have been quantified by means of molecular dynamics simulation to be as large as 0.6 eV. [ 61 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the smaller energy gap combined with the increased SOC leads to the increased importance of direct ISC in 15. This simplifies the mechanism for triplet harvesting and also removes the strong environment effects observed in D-A molecules [68][69][70][71][72][73][74][75] making it easier to develop high throughput design rules.…”
Section: Excited States Properties Of 13 14 and 15mentioning
confidence: 99%
“…13 More recent follow-up modelling work by Yang et al showed that SSSE may still play a larger role than initially predicted but it remains a weak effect compared to standard solution polarity effects. 14 Etherington et al investigated the photophysics of 4CzIPN in more detail, looking at potential dimer formation that could lead to the shift of the CT emission. 15 Sublimation of pristine 4CzIPN led to the formation of several fractions, all of them crystal polymorphs with different emission properties in which the carbazole units of separate molecules were found to show partial or full face-to-face overlap to form dimer species.…”
Section: Introductionmentioning
confidence: 99%